انسانية الامير عبدالقادر في تعاملاته مع الاخر 1832-1883م - فاطمة الزهراء سعدي; د/ احمد سعودي (جامعة عمار ثليجي بالاغواط, 2025)
باللغة العربية: يتميز هذا الموضوع على ابراز مساهمة الامير عبدالقادر الجزائري في ترسيخ القيم الانسانية والمعاملة الحسنة أثناء الحروب، وذلك من خلال سعيه للسلام وسد أسباب الحرب، والحد من اراقة الدماء وخسارة الارواح واقراره لشرعية وقدسية الحرب الدفاعية والسعي للحوار والتفاوض كإجراء ضروري ودعى لاحترام الكرامة الانسانية للسجناء وحماية حياتهم وكرامتهم وحرية دينيهم ومعتقداتهم، وتوفير الامن والمأكل والملبس لهم كشرط من شروط عملية الاسر ومنح جنوده مكافآت مالية لتقليل عدد القتلى من العدو بزيادة عدد الاسرى اضافة إلى جانب تنمية القيم الانسانية مع موافقة الاخلاقية أثناء الحرب. باللغة الأجنبية: This topic is distinguished by highlighting the contribution of Prince Abdelkader Al-Jazairi to consolidating human values and good treatment during wars, through his pursuit of peace, bridging the causes of war, reducing bloodshed and loss of life, his recognition of the legitimacy and sanctity of defensive war, and the pursuit of dialogue and negotiation as a necessary measure, and he called for respecting the human dignity of prisoners and protecting their lives.Their dignity and freedom of religion and beliefs Providing them with security, food, and clothing as a condition for the capture process, and granting his soldiers financial rewards to reduce the number of enemy deaths by increasing the number of prisoners, in addition to developing human values with moral approval during war.